2016
DOI: 10.2319/090315-593.1
|View full text |Cite
|
Sign up to set email alerts
|

Variation in form of mandibular, light, round, preformed NiTi archwires

Abstract: Objective: To evaluate the variation in form of nickel-titanium (NiTi) archwires by comparing them with the dental arch form of normal Japanese subjects before and after placing them in the first molar tubes. Materials and Methods: The mandibular dental casts of 30 normal subjects were scanned, and the dental arch depths and widths from the canine to the first molar were measured. Standardized images of 34 types of 0.016-inch preformed NiTi archwires were also taken in a 37uC environment, and the widths were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
(26 reference statements)
2
8
0
Order By: Relevance
“…Preserving the dental arch form during orthodontic treatment is an important factor in the stability of the treatment outcome. 7 Unplanned contraction or expansion, especially at the intercanine and intermolar regions, can lead to instability. 8,14,15 Thus, correct selection of the primary archwire at the onset of treatment is highly important.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preserving the dental arch form during orthodontic treatment is an important factor in the stability of the treatment outcome. 7 Unplanned contraction or expansion, especially at the intercanine and intermolar regions, can lead to instability. 8,14,15 Thus, correct selection of the primary archwire at the onset of treatment is highly important.…”
Section: Discussionmentioning
confidence: 99%
“…16 Also, racial differences that cause variations in dimensions and form of dental arch compared with the available archwires further highlight the significance of proper selection of a preformed archwire that best fits the dental arch. 7,17,18 Diagnostic software programs can provide accurate information and aid in determining more complex patterns of arch form. In addition, advances in computer analyses enable better definition of arch form individually for each patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Means and standard deviations (SDs) of the normal canine depth (4.84 mm ± 0.70 mm) and mean first molar depth (26.66 mm ± 1.57 mm) at the bracket slot (BS) points, which represented the position of the base of the bracket slot of the dental arch form of subjects with normal occlusions, were established based on our previous studies [ 14 , 21 ]. Means ± SDs as the normal ranges for ICWs (30.18 mm ± 1.32 mm) and IMWs (55.72 mm ± 2.66 mm) of the dental arch form were also established using data from the same previous studies [ 14 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Most orthodontists selected archwires subjectively by visual assessment of the adaptation of the archwires to the facial axis or facial surface of the teeth, incisal edges and cusp tips, or the facial portion of the proximal contacts. 5,[10][11][12] One study showed wide variation in the dimensions of working archwires fabricated on identical dental casts using subjective assessment among 30 clinicians. 13 McNamara et al 6 raised a question regarding the possibility of using digital models for accurate archwire selection.…”
Section: Introductionmentioning
confidence: 99%